Gene-specific monitoring of T7-based RNA amplification by real-time quantitative PCR - Sandra G. Heil; Leo A.J. Kluijtmans; Ofer Spiegelstein; Richard H. Finnell; Hank J. Blom (BioTechniques)
T7-based RNA amplification is applied when there is insufficient RNA. The overall extent of amplification can be measured spectrophotometrically (i.e., quantifying RNA yields), but this measurement does not provide information about the RNA amplification of individual genes. Here we describe a method applying real-time quantitative PCR, which enables the monitoring of RNA amplification of individual genes. The amount of RNA before and after T7-based RNA amplification was determined by real-time quantitative PCR for three housekeeping genes: β-2-microglobulin, porphobilinogen deaminase, and serine dehydratase, which are, respectively, a high, intermediate/low, and low copy transcript. Real-time quantitative PCR appeared to be suitable to determine the extent of RNA amplification, as was reflected by the low intra- and inter-run coefficients of variation of cycle threshold of 1.1%–2.1%. The application of real-time quantitative PCR showed that T7-based RNA amplification is reproducible but might introduce a sequence-specific bias. Real-time quantitative PCR is a novel approach to monitor RNA amplification and is particularly suited to study RNA amplification of individual genes.